Microbial succession and the changes of flavor and aroma in Chouguiyu, a traditional Chinese fermented fish. (October 2020) - Yang, Zhaoxia; Liu, Sasa; Lv, Jing; Sun, Zeping; Xu, Wenhuan; Ji, Chaofan; Liang, Huipeng; Li, Shengjie; Yu, Chenxu; Lin, Xinping
Abstract: Chouguiyu (stinky Mandarin fish), a traditional spontaneously fermented fish in China, is famous for its unique aroma and pleasant taste. However, the relationships between the succession of microorganisms during the fermentation and the formation of Chouguiyu 's unique aroma and taste remain to be characterized. In this study, 16S rRNA gene amplicon sequencing was done to investigate the evolving microbiota during Chouguiyu fermentation, and the volatile compounds and amino acids profiles were measured alongside with chemical characterization of the samples (e.g., determination of pH, TVB-N, TBARS, and TCA-soluble peptides). Based on the changes of the microbiota, the fermentation was categorized into two stages: early-fermentation, 1st-3rd days; and late-fermentation, 4th-7th days. Linalool, piperitone, anethole, 1-octen-3-ol, 2-methyl-3-octanone and indole were identified as characteristic volatile compounds in Chouguiyu . According to the sensory evaluation results, the flavor of the Chouguiyu was reinforced in the late-fermentation stage. Redundancy analysis showed the relationships between evolving microbiota and the formation of Chouguiyu 's aroma and taste, and Psychrilyobacter was identified to be the most important bacterial genus contributing to flavor and aroma development, followed by Fusobacterium, Arcobacter and O c eanisphaera . These genera were positively correlated with Glu, Met, Tyr, Pro, linalool, piperitone, indole, TBARS, TVB-N, and TCA, and influenced the flavor and aroma of the Chouguiyu . The results of this study provided a scientific basis to further improve Chouguiyu production. Highlights: Chouguiyu 's fermentation process was divided into early-fermentation and late-fermentation. The changes of features in Chouguiyu were more pronounced during the late-fermentation stage. Four genera were found to be highly related to the change of Chouguiyu' s flavor and aroma. These 4 genera included Psychrilyobacter, Fusobacterium, Arcobacter and Oceanisphaera . The Psychrilyobacter was highly related to the flavor and aroma of Chouguiyu .